Abundance of ants (hymenoptera : formicidae ) in UiTM Kuala Pilah, Negeri Sembilan / Nurshuada Yunus - Yunus, Nurshuada (2018)
Ants are dominant group of insect that can be found anywhere except for polar region. There are few factors that contribute toward habitation of ants at an area such as soil, temperature and resources. Ants have 22 subfamilies and each of them have their own habitat preferences and feeding behavior. This study aims to determine the abundance of ants in UiTM Kuala Pilah. Method used in this study is bait-fall trap. It is recommended compared to manually captured ants because it is accurate. This is because ants have different timing of foraging. By using bait-fall trap, we are able to captured ants with different foraging behavior because the trap is left for 24 hours. From the result, there are three subfamilies exist in UiTM Kuala Pilah. Each area has different resources availability. This contributes to the abundance of ants at an area. Ants choose habitat by considering the amount of disturbance occur in an area. One of the areas has low abundance due to high human interaction in the area. The ants migrate its nesting to other area that offers resources and have less disturbance in order to have high chances of survival.